PEMBERDAYAAN MASYARAKAT PESISIR PETANI RUMPUT LAUT DI DESA MANYAMPA KECAMATAN UJUNG LOE KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The main problem in this project is the empowerment of coastal communities of seaweed farmers in Manyampa Village, Ujung Loe District, Bulukumba Regency. The main problem is described in several sub-problems, namely; 1) How are the efforts of the coastal communities of seaweed farmers in improving their lives? 2) What are the government’s efforts to support the welfare of seaweed farmers in Manyampa Village, Ujung Loe District, Bulukumba Regency? This type of research is included in qualitative research using the approach method, namely the sociological approach. Furthermore, the data sources are primary data and secondary data. Then the data methods used were observation, interviews, and documentation. Then the data processing and analysis techniques were carried out through three stages data reduction, data presentation (data display), and drawing conclusions. The results showed that one of the impacts felts by seaweed farmers cultivating seaweed was that the coastal community’s economy itself increased and was able to cover the daily needs of the coastal community of seaweed farmers. Elementary school to a higher level up to college. The role of the government in cultivating seaweed is felt by seaweed farmers themselves. The government acts as a) Capital Assistance b) Opening job opportunities c) Coordinator d) Facilitator and e) Motivator. The implication of this research is the author hopes for seaweed farmers to learn more and understand better seaweed farming methods so that the quality of seaweed will increase, as well as for the seaweed buyers to better determine the price of seaweed itself and be more evenly distributed. Purchase of the seaweed. For the government to improve the facilities and infrastructure needed by seaweed farmers in cultivating seaweed, it is also expected to always educate the public to maintain seaweed cultivation and teach the younger generation to continue cultivating and maintaining the quality of the seaweed.